Tuning Intramolecular Förster Resonance Energy Transfer and Activating Intramolecular Singlet Fission - Lavarda, Giulia; Zirzlmeier, Johannes; Gruber, Marco; Rami, Parisa R.; Tykwinski, Rik; Torres, Tomas; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2018)
The synergy of panchromatic absorption throughout most of the visible range of the solar spectrum and intramolecular singlet fission (SF) has been realized in a series of conjugates featuring different light-harvesting subphthalocyanines (SubPcs) and an energy accepting pentacene dimer (Pnc2). At the focal point was a modular SubPc approach, which was based on decorating the SubPc core with different peripheral substituents to tailor and fine-tune their optical properties. Transient absorption measurements assisted in corroborating that the SubPcs act as energy-transfer antennas by means of unidirectional and quantitative intramolecular Förster resonance energy transfer (FRET) to the Pnc2, where an intramolecular SF affords triplet quantum yields reaching unity.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Förster resonance energy transfer; intramolecular singlet fission; photochemistry; transient absorption spectroscopy